Enhancing growth, yield and water use efficiency of rice (Oryza sativa) through drip irrigation - SUBRAMANIAN, E; RAMESH, T; VIJAYAKUMAR, S; RAVI, V (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during rainy (kharif) season of 2018 and 2019 at the research farm of Tamil Nadu Rice Research Institute, Aduthurai, Tamil Nadu to evaluate the impact of drip irrigation on rice (Oryza sativa L.) growth, productivity and water use efficiency. The experiments were laid out in a strip plot design with 4 varieties/hybrids in the horizontal strip and 6 irrigation regimes in the vertical strip with 3 replications. The findings reveal that drip irrigation at 125% Pan Evaporation (PE) resulted in superior growth, yield parameters and grain yield. KRH 2 with 125% PE recorded the maximum grain yield (4200 kg/ha), followed by ADT 45 (4140 kg/ha) with 125% PE. All yield attributes, except ill-filled grains/panicle, increased with increasing irrigation level from 50 to 125% PE. Rice yield attributes, viz. tillers/m2 (r=0.86), panicles/m2 (r=0.90) and grains/panicle (r=0.84) showed positive correlation with grain yield. Irrespective of the variety and irrigation levels the row closer to the drip line recorded higher grain yield at all the irrigation levels compared to rows farthest. Among the irrigation regime the highest total water use (671 mm) was recorded in 125% PE while the highest water use efficiency (6.5 kg/ha-mm) was recorded in 75% PE up to tillering stage, 100% PE during flowering phase and 75% PE during maturity phase. Among the variety, ADT 45 recorded the highest water use efficiency (7.15 kg/ha mm). The study recommends KRH 2 hybrid and ADT 45 variety for drip irrigation with 125% PE in areas with limited water availability, especially in well-irrigated areas.